2022
DOI: 10.24875/ciru.22000303
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose Cordyceps on ischemia-reperfusion injury of the kidney in rats

Abstract: Objective: None of studies have been conducted in terms of demonstrating the same effect with the low dose in cordycepin. In our study, we analyzed the histopathological and biochemical changes of low-dose Cordycepin(c) on a rat model in the kidney. Materials and methods: Twenty-four male Wistar Albino rats were randomly allocated to three groups (n = 8): the sham-control group (Group 1), the renal I/R-untreated (Group 2) group, and the I/R-C-treated (Group 3) group. Cordyceps was administered intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The study of Okur et al 5 found that cordycepin significantly reduced TNF-α and MDA levels and increased TAS while decreasing TOS in the testicular tissue of rats subjected to I/R, compared to the I/R group without cordycepin treatment, indicating its potential protective effect against I/R-induced testicular damage. Özgür et al 6 study highlighted that both ibuprofen and roflumilast offer protective effects as antioxidant treatments in testicular ischemia-reperfusion injury, with roflumilast demonstrating superior benefits.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The study of Okur et al 5 found that cordycepin significantly reduced TNF-α and MDA levels and increased TAS while decreasing TOS in the testicular tissue of rats subjected to I/R, compared to the I/R group without cordycepin treatment, indicating its potential protective effect against I/R-induced testicular damage. Özgür et al 6 study highlighted that both ibuprofen and roflumilast offer protective effects as antioxidant treatments in testicular ischemia-reperfusion injury, with roflumilast demonstrating superior benefits.…”
Section: Discussionmentioning
confidence: 95%
“…Given that the length of the torsion is strongly related to the chance of losing a testicle, prompt surgical intervention is absolutely necessary. In an effort to reduce IR damage related to TT, several strategies have been used such as cordycepin, roflumilast and ibuprofen, arbutin, thymoquinone, and syringic acid [4][5][6][20][21][22] . However this is the first study To the best of our knowledge, this is the first study administering PI to rats in a testis torsion-induced model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] Cordycepin (COR), the main active component of C. sinensis, is also a kind of pharmacologically active small molecules, whose role and targets in kidney injury have rarely been reported so far. [6,7] Despite being one of the most effective chemotherapeutics for treating solid tumors, the application of cisplatin (CDDP) in chemotherapy is restricted by its histotoxicity, especially kidney toxicity, with CDDP-induced acute kidney injury (AKI) seriously affecting the chemotherapeutic efficacy and quality of life of patients. [8] Studies have found that ferroptosis is one of the primary mechanisms whereby CDDP induce kidney injury, while inhibiting ferroptosis can inhibit CDDP-induced kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4,5 ] Cordycepin (COR), the main active component of C. sinensis , is also a kind of pharmacologically active small molecules, whose role and targets in kidney injury have rarely been reported so far. [ 6,7 ]…”
Section: Introductionmentioning
confidence: 99%